Adult non-urethral complications after hypospadias repair in childhood: presentation, treatment and outcomes - Stojanovic, Borko; Bizic, Marta; Bencic, Marko; Djordjevic, Miroslav L. (Frontiers in Endocrinology, 2023)
Purpose This study aimed to evaluate a group of adult patients with non-urethral complications after hypospadias repair in childhood, their surgical treatment, and outcomes. Materials and methods We analyzed 97 patients, mean age 22.5 years, who were treated in our center between January 2009 and December 2020, for non-urethral complications after previous hypospadias repair in childhood. Non-urethral complications were defined as glans deformity, residual curvature and trapped penis due to insufficient penile skin. A radical surgical approach was used to correct all deformities, in a one-stage or a two-stage procedure. A successful outcome was defined as a straight penis with good length, anatomically regular glans, and cosmetically acceptable appearance, without need for additional surgeries. Sexual function was evaluated using International Index of Erectile Function. Results Mean follow-up was 75 months (ranged from 24 to 168 months). One-stage and two-stage repair were performed in 85.5% and 14.5% of cases, respectively. A higher success rate was noted after one-stage repair (94% compared to 86%). Complications included four cases of penile curvature with late onset, one case of glans dehiscence and partial skin necrosis. Erectile dysfunction was determined in 24% of patients. Discussion Non-urethral complications may occur many years after primary hypospadias repair, with a strong impact on the quality of life. Treatment is individualized and usually involves a radical surgical approach to correct all associated deformities and to achieve successful cosmetic and psychosexual outcomes.